2022
DOI: 10.3389/fnmol.2022.832813
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Temporal Analysis of Single-Cell RNA Sequencing Reveals Trans-Differentiation Potential of Greater Epithelial Ridge Cells Into Hair Cells During Postnatal Development of Cochlea in Rats

Abstract: The hair cells of the cochlea play a decisive role in the process of hearing damage and recovery, yet knowledge of their regeneration process is still limited. Greater epithelial ridge (GER) cells, a type of cell present during cochlear development that has the characteristics of a precursor sensory cell, disappear at the time of maturation of hearing development. Its development and evolution remain mysterious for many years. Here, we performed single-cell RNA sequencing to profile the gene expression landsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…They found that the neonatal cochlear stem cell gene ( Lgr5 ) was highly expressed in outer GER cells, suggesting that GER cells may be a precursor cell pool for cochlear HC regeneration. Chen et al further identified eight subtypes of GER cells through scRNA-seq, four of which continuously increased in cell number from P1 to P7 but incrementally decreased and disappeared at P14, and all highly expressed genes were related to hearing loss, such as Col2a1 , Col9a1 , Col9a2 and Col11a2 , especially two of these subtypes mainly differentiated into OHCs with highly expressed genes Crym , Col9a2 , Col2a1 , Col9a1 , Cytl1 , Cnmd , Serpinf1, and Col11a2 , respectively, but other two subtypes ( Lepr , Ramp3 ; Igfbp4 ) ultimately differentiated into IHCs [ 103 ].…”
Section: Application Of Scrna-seq In Other Types Of Inner Ear Cellsmentioning
confidence: 98%
“…They found that the neonatal cochlear stem cell gene ( Lgr5 ) was highly expressed in outer GER cells, suggesting that GER cells may be a precursor cell pool for cochlear HC regeneration. Chen et al further identified eight subtypes of GER cells through scRNA-seq, four of which continuously increased in cell number from P1 to P7 but incrementally decreased and disappeared at P14, and all highly expressed genes were related to hearing loss, such as Col2a1 , Col9a1 , Col9a2 and Col11a2 , especially two of these subtypes mainly differentiated into OHCs with highly expressed genes Crym , Col9a2 , Col2a1 , Col9a1 , Cytl1 , Cnmd , Serpinf1, and Col11a2 , respectively, but other two subtypes ( Lepr , Ramp3 ; Igfbp4 ) ultimately differentiated into IHCs [ 103 ].…”
Section: Application Of Scrna-seq In Other Types Of Inner Ear Cellsmentioning
confidence: 98%
“…GER cells have the characteristics of prosensory cells, and Kubota et al used single-cell RNA sequencing to determine different cochlear cell types in neonatal mice and to evaluate their potential to transform into inner ear organoids and identified three distinct groups of large epithelial crest cells with the ability to differentiate into inner ear organoids under high-density conditions [ 108 ]. Chen et al used single-cell RNA sequencing to reveal the differentiation of eight cell subtypes from GER cells, two of which transdifferentiate predominantly into inner hair cells and two subtypes that ultimately differentiate into OHCs [ 109 ]. Iyer et al found that some of the GER cells are not able to transform into hair cells, and this is partially due to the reconstitution of the Notch signaling interactions between newly-formed hair cells and GER cells [ 27 ].…”
Section: Stem Cells For Hair Cell Regenerationmentioning
confidence: 99%
“…Zebrafish (transgenic model for HC ablation) [164] Identification of genes associated with Tmprss3-related hearing loss Mouse (Tmprss3-KO organoids) [127] Delineation of key regulatory mechanisms in HC regeneration Rats [186] Spatial transcriptomics Single-molecule FISH (smFISH) Annotating distinct transcriptome of SC populations in specific anatomic locations of the cochlea Mouse [131] Whole-mount ISH Spatiotemporal cadence of key signaling pathways in the context of developmental processes of the cochlea Mouse organotypic cultures [132] Genetically engineered mouse models of genes related to developmental processes [129] Uncovering quantitative differential transcriptional profile in pre-mature and mature HCs, revealing novel role of genes in the differentiation process Mice (P4 and 3 weeks old) [130] LCM…”
Section: Identification Of Gene Regulatory Network Involved In Hc Reg...mentioning
confidence: 99%